COMBINATION OF ESZOPICLONE AND MIND-BODY THERAPY AS NOVEL STRATEGY IN INSOMNIA TREATMENT - Dwi Putra, AAD Dalem (E-Jurnal Medika Udayana; vol 2 no1 (2013):e-jurnal medika udayana)
Insomnia is defined as a disorder of difficulty initiating sleep, difficulty maintaining sleep, sleep is not fresh during 1 month or more that makes a significant clinical disturbance or distress. Insomnia affects 15% to 40% of world general population and predominantly in women 65 to 79 years. Insomnia also reported in individuals aged 18 to 34 years. If neglected for a long time, insomnia can diminish job performance and quality of live for each individuals. The new strategy to solve this problem in the future is combining pharmacotherapy like eszopiclone a nonbenzodiazepine derivate and mind-body therapy (MBT) to the patients. It can lowering severe risk of conventional drugs side effects, but from pharmacoeconomic this drug is not costly effective. It must combine with MBT to decrease frequency and duration of drug consumption.
Keywords: insomnia, eszopiclone, mind-body therapy